Reverse privatization as a reaction to the competitive environment: Evidence from solid waste collection in Germany - Juri Demuth; Hans Friederiszick; Steffen Reinhold (European School of Management and Technology (ESMT), 2018)
After earlier waves of privatization, local governments have increasingly taken back control of local service provisions in some sectors and countries and, instead, started providing those services themselves (reverse privatization). Using a unique panel data set on the mode of service provision for solid waste collection for German municipalities covering the years 2003, 2009, and 2015, we investigate motives for reverse privatization. Our results show that, in deciding whether to insource or not, municipalities react to the cost advantages of private suppliers as well as to the competitive environment, with more switching to insourcing in concentrated markets. Furthermore, we find local contagion effects, that is, insourcing is more likely if municipalities close by also provide services themselves, whether in horizontally or vertically-related markets. Implications for competition law enforcement are discussed.
urn:nbn:de:101:1-201804279195
Keywords: L33; L44; L88; H44; K21; 650; local privatization; state-owned enterprises; competition law enforcement; mergers; logit regression